13. Optical coherence tomography and multifocal visual evoked potential clinical usefulness in identifying visual pathway involvement. Issue 4 (April 2016) - Guerrieri, S.; Di Maggio, G.; Vitali, F.; Santangelo, R.; Medaglini, S.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; Leocani, L.
Abstract : Full-field visual evoked potentials (ff-VEP) are fundamental in neurological practice, for defining the nature of visual disturbances. We explored whether, in case of normal ff-VEP and suspected organic visual pathway involvement, multifocal visual evoked potentials (mf-VEP) and optical coherence tomography (OCT) can be useful in the diagnostic workup. Observational case reports on 3 patients presenting with visual disturbances. Two had relapsing optic neuritis (ON) and visual acuity (VA) loss, with normal or non-significant ff-VEP outside acute clinical episodes. In both cases OCT showed a retinal nerve fiber layer (RNFL) thickness reduction, allowing visual pathway damage identification. The third, with meningioma involving left optic nerve, complained of blurred vision in the nasal field of the left eye as confirmed by computerized perimetry (CP). While ff-VEP showed normal latency and non-significant amplitude reduction in the left eye, mf-VEP showed important amplitude reduction in the lower visual field of the left eye. OCT scan confirmed axonal damage showing left RNFL thinning. Sometimes ff-VEP fails in identifying abnormalities in patients with pathologic processes involving the visual pathway, particularly in cases with axonal or sectorial optic nerve involvement. We suggest the importance of a multimodal evaluation, including OCT and mf-VEP.